2024
DOI: 10.5772/intechopen.112594
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Delay in Construction Projects

A.M. Faten Albtoush

Abstract: The construction sector is considered the most important sector, as it contributes to raising the country’s economy. Therefore, it is necessary to search for the obstacles. One of these obstacles is the delay, as the project is rarely completed within the planned period. Among the most prominent reasons for this delay are change orders, financial problems for the owner, and slow decision-making on the part of stakeholders. This delay led to various risks, like financial risks, which were represented in exceedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
(20 reference statements)
0
2
0
Order By: Relevance
“…The authors noted that delays are one of the main areas of scientific research due to the impact of delays on the time and cost of implementing construction projects. In publication [4], the risk of delays in construction projects has been discussed. The authors have identified several main causes of delays, such as order changes, the owner's financial problems, and slow decision-making by stakeholders.…”
Section: A Review Of Knowledge Of Metaheuristics In Engineeringmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors noted that delays are one of the main areas of scientific research due to the impact of delays on the time and cost of implementing construction projects. In publication [4], the risk of delays in construction projects has been discussed. The authors have identified several main causes of delays, such as order changes, the owner's financial problems, and slow decision-making by stakeholders.…”
Section: A Review Of Knowledge Of Metaheuristics In Engineeringmentioning
confidence: 99%
“…In this particular situation, such a combination can be used to optimize various aspects of the construction process, such as schedule planning, resource management, or building structure design. As a result, it is possible to achieve better effects, such as shorter construction times, lower costs, or better quality of construction [4,10].…”
Section: Justification Of the Research Fieldmentioning
confidence: 99%